Clinical characteristics of non-idiopathic pulmonary fibrosis, progressive fibrosing interstitial lung diseases: A single-center retrospective study. Issue 13 (2nd April 2021) - Komatsu, Masamichi; Yamamoto, Hiroshi; Kitaguchi, Yoshiaki; Kawakami, Satoshi; Matsushita, Mina; Uehara, Takeshi; Kinjo, Takumi; Wada, Yosuke; Ichiyama, Takashi; Urushihata, Kazuhisa; Ushiki, Atsuhito; Yasuo, Masanori; et al.
Abstract : Abstract: Progressive fibrosing interstitial lung disease (PF-ILD) is a progressive phenotype of fibrosing ILDs with varying definitions and elusive clinical characteristics. We aimed to clarify the clinical features and prognosis of PF-ILD cases based on the deterioration of pulmonary function. Altogether, 91 consecutive ILD patients who underwent at least 2 pulmonary function tests (PFTs) with an interval of at least 24 months, as the screening period, between January 2009 and December 2015 were retrospectively reviewed. The deterioration of forced vital capacity (FVC) and diffusing capacity of the lung for carbon monoxide (DLco) was calculated based on PFT data and screening period. The definition of PF-ILD was relative decline of 10% or more in FVC per 24 months or relative decline in FVC of 5% or more with decline in DLco of 15% or more per 24 months. Medical records of 34 patients with idiopathic pulmonary fibrosis (IPF), 11 patients with non-IPF, PF-ILD, and 46 patients with non-IPF, non-PF-ILD were retrospectively analyzed. Patient characteristics, pharmacologic or non-pharmacologic treatment status, and prognosis were compared between the IPF and non-IPF groups and between the non-IPF, PF-ILD and non-IPF, non-PF-ILD groups. Eleven patients (19.3%) showed a progressive phenotype in the non-IPF group. The pulmonary function data at the first PFT were worse in non-IPF, PF-ILD patients than in non-IPF, non-PF-ILD patients. There were no differences in the proportion of patients who were observed without pharmacologic treatment or of those receiving pharmacologic treatment between the non-IPF, PF-ILD and non-IPF, non-PF-ILD groups. Low %FVC at the first PFT and the usual interstitial pneumonia-like fibrotic pattern on high-resolution computed tomography were risk factors for PF-ILD in the non-IPF group. The mortality in the non-IPF, PF-ILD group was significantly worse than that of the non-IPF, non-PF-ILD group and was as poor as that of the IPF group. Multivariate logistic analysis showed that aging and low %DLco at the first PFT were risk factors for mortality within the non-IPF group. The prognosis of non-IPF, PF-ILD patients was as poor as that of IPF patients. Non-IPF, PF-ILD patients require more intensive treatment before disease progression.